Pengaruh Latihan Zig Zag Run Terhadap Kecepatan Tendangan Sabit Pencak Silat - Azizah, Nurhasanah; Vai, Aref; Maesaroh, Siti (STAMINA, 2024)
Martial arts are known for their rapidity, which is advantageous for maneuvering swiftly and assuming attacking postures. As such, this speed has a high probability of success. This study set out to ascertain how zig zag run training affected sickle kick agility in the Rokan Hilir PSHT pencak silat sport. This research has been carried out from November 2023 to March 2024. This study employed a one-group pretest-posttest design technique after utilizing an experimental method with a control group. In this study, up to ten participants were chosen at random from the entire population using the total sampling approach. A t-test was used to examine the research data after a sickle kick speed test was used to collect the data. Based on a discussion and analysis of the research findings, it was determined that zig-zag run training significantly increased the sickle kick speed of the Rokan Hilir Branch PSHT college, with a significance value of 0.05 at 95% confidence and a t-count of 10.641. Therefore, the hypothesis proposed earlier Ha stated that it was accepted, so it is expected to increase the agility of the sickle kick with the method of several agility exercises, one of which is with zig-zag run training as one of the strategies for attacking